Microfilm edition of the papers of Henry Lewis Stimson (not including the diaries) in the Yale University Library - Stimson, Henry L. (Henry Lewis), 1867-1950 (Yale University Library, Manuscripts and Archives, 1973)
Correspondence, speeches and writings, memoranda, minutes of meetings, notes on conversations and interviews, special subject files, selected State Dept. documents, and other papers relating to Stimson's interests and activities in a long life of public service, including his New York law practice, his service as U.S. Attorney in New York (1906-1909), Secretary of War under William Howard Taft (1911-1913), Governor-General of the Philippines (1927-1929), Secretary of State under Herbert Hoover (1929-1933), and Secretary of War under Franklin D. Roosevelt and Harry Truman (1940-1945)